Economic Report on Africa 2013 - United Nations (United Nations, 2013)
Africa’s growth plummeted during its ‘lost decades’ of the 1980s and 1990s while unemployment soared, and production and export bases became more concentrated. Africa boasts significant human and natural resources that can be used to promote industrialization and structural economic transformation through value-addition strategies in all sectors. This publication examines key constraints and opportunities for African countries to make the most of their commodities by adding value through linkage development. It also addresses how African countries can design and implement policies to promote value addition and economic transformation, and reduce their dependence on producing and exporting unprocessed commodities.